Effectiveness of influencer marketing tactics and our understanding of consumers psychology in the digital era - Muhammad Ashraf, Fauzi; Farghaly, Ahmed Taiseer; Nur Sofia Nabila, Alimin (URBE, 2024)
Social media became very popular lately and social media influencers became a main driver in the marketing strategies in the last years, they also have the ability to influence a wild numbers of audience behaviours and their preference when it comes to purchasing decisions and all this became possible because of social media platforms such as Facebook, Instagram, YouTube and TikTok, This paper aims to improve our knowledge of marketing through social media influencers by studying how influencer attributes effects customers behaviour, attributes such as expertise, trustworthiness, similarities, and attractiveness , this paper will provide some important ideas on how to improve influencers marketing strategies and will make us understand customers purchasing behaviour, the results of this paper might deliver a very useful insights on how to develop brands ethical marketing and will provide suggestions to help brands in implementing influencers marketing in their marketing strategies to be able to reach their target audience through better and real cost efficient manner